AC failure voltage of iced and contaminated composite insulators in different natural environments. (September 2020) - Qiao, Xinhan; Zhang, Zhijin; Jiang, Xingliang; Sundararajan, Raji; Ma, Xiaodan; Li, Xun
Highlights: Flashover tests of iced and contaminated insulators were conducted at Natural Test Base . AC failure voltage in 5 nature conditions of composite insulators were obtained. The flashover process of insulators in different environments were recorded and analyzed. The gradient flashover voltage Eα were calculated based on the test results. Abstract: It is found that some composite insulators with faults in transmission lines have no defect when they are tested in the laboratory, so there is a certain difference between the laboratory and the actual transmission lines. Accordingly, in this paper, flashover tests of natural iced and contaminated composite insulators were conducted at Xuefeng Mountain Natural Icing Test Base in different natural environments, which overcomes the shortcomings of traditional laboratory simulation test methods. Then, AC failure voltages in 5 natural conditions (Dry, rime ice, pollution in cold fog, glaze-ice without icicles and glaze-ice with icicles) of composite insulators were obtained. In addition, the flashover processes in typical conditions were recorded and analyzed. Finally, withstand voltages with different failure probabilities were calculated. The results indicate that the flashover voltage varies greatly in different environments. The maximum flashover voltage is 2.43 times more than the minimum. Besides, both rime ice and dry flashover voltage and equivalent salt deposit density (ESDD) are independent of each other. But there is a negative power function (NPF) relationship between both pollution and glaze-iced flashover voltage and ESDD in natural environment. What's more, compared with exponential function, power function is more suitable for fitting function between glaze-ice flashover voltage and glaze-ice weight. Last, the gradient flashover voltage E α with α% failure probability can be calculated by tested flashover voltages through variable substitution. Further, E10, E5 and E(μ-3σ) were obtained which can provide important guidance for insulation design in different natural environments.